### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

The roots of x^2 + 5x + 6 = 0 are -2 and -3.

To find the roots of a quadratic equation in the form ax^2 + bx + c = 0, we can use the quadratic formula:

x = (-b ± √(b^2 - 4ac)) / 2a

In this case, a = 1, b = 5, and c = 6. Substituting these values into the quadratic formula, we get:

x = (-5 ± √(5^2 - 4(1)(6))) / 2(1)

Simplifying the expression under the square root:

x = (-5 ± √1) / 2

We can see that the expression under the square root simplifies to 1, so:

x = (-5 ± 1) / 2

This gives us two possible values for x:

x = (-5 + 1) / 2 = -2

x = (-5 - 1) / 2 = -3

Therefore, the roots of the quadratic equation x^2 + 5x + 6 = 0 are -2 and -3.

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...